The male fetal biomarker INSL3 reveals substantial hormone exchange between fetuses in early pig gestation - Vernunft, Andreas; Ivell, Richard; Heng, Kee; Anand-Ivell, Ravinder (Public Library of Science, 2016)
The peptide hormone INSL3 is uniquely produced by the fetal testis to promote the transabdominal phase of testicular descent. Because it is fetal sex specific, and is present in only very low amounts in the maternal circulation, INSL3 acts as an ideal biomarker with which to monitor the movement of fetal hormones within the pregnant uterus of a polytocous species, the pig. INSL3 production by the fetal testis begins at around GD30. At GD45 of the ca.114 day gestation, a time at which testicular descent is promoted, INSL3 evidently moves from male to female allantoic compartments, presumably impacting also on the female fetal circulation. At later time-points (GD63, GD92) there is less inter-fetal transfer, although there still appears to be significant INSL3, presumably of male origin, in the plasma of female fetuses. This study thus provides evidence for substantial transfer of a peptide hormone between fetuses, and probably also across the placenta, emphasizing the vulnerability of the fetus to extrinsic hormonal influences within the uterus.